Reactivity of phospha–Wittig reagents towards NHCs and NHOs. Issue 5 (20th January 2021) - Gupta, Priyanka; Siewert, Jan-Erik; Wellnitz, Tim; Fischer, Malte; Baumann, Wolgang; Beweries, Torsten; Hering-Junghans, Christian
Abstract : Phospha–Wittig reagents of the type RPPMe3 can be considered as phosphine-stabilized phosphinidenes and were shown to react with NHCs and NHOs to afford NHC phosphinidene adducts or P-substituted NHOs, respectively. Abstract : Phospha–Wittig reagents, RPPMe3 (R = Mes* 2, 4, 6- t Bu3 -C6 H2 ; Mes Ter 2, 6-(2, 4, 6-Me3 C6 H2 )-C6 H3 ; Dip Ter 2, 6-(2, 6-iPr2 C6 H3 )-C6 H3 ), can be considered as phosphine-stabilized phosphinidenes. In this study we show that PMe3 can be displaced by NHCs or NHOs. Interestingly, phosphinidene-like reactivity results in a subsequent C(sp 2 )–H activation of the exocyclic CH2 group in NHOs. This concept was further extended to allyl-apended NHOs, which resulted in phosphine-substituted allyl species.